A COST-BENEFIT ANALYSIS OF POMEGRANATE PRODUCTION IN SANGLI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The pomegranate crop obtained a great significance due to the large suitability in drought prone region of Sangli district.In the present study, an attempt has been made to assess the cost-benefit ratio of pomegranate production in Sangli district. Cost-benefit analysis is a method used in farming to evaluate the potential profitability of any crop and it plays an important role in encouraging particular crop enterprises.Pomegranate cultivation is practiced more or less throughout the Sangli district but Atpadi, Jat, Kavathe Mahankal, Miraj and Khanapur tahsils are the major pockets of these fruit crops.